2008
DOI: 10.1007/s12029-009-9067-x
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Radiotherapy Planning Modality Influences Toxicity in the Treatment of Locally Advanced Esophageal Cancer

Abstract: 3DCTP reduces acute esophagitis in patients receiving multimodality therapy for esophageal cancer without compromising clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…3D treatment planning and a multiple portal technique may reduce toxicities related to radiation. Mackley et al reported reduced acute esophagitis in patients with locally advanced esophageal cancer, due to the 3D treatment planning [16]. We infer that 3D treatment planning with 3-or 4-portals used in the IFI group might contribute to lower incidences of late toxicities.…”
Section: Discussionmentioning
confidence: 72%
“…3D treatment planning and a multiple portal technique may reduce toxicities related to radiation. Mackley et al reported reduced acute esophagitis in patients with locally advanced esophageal cancer, due to the 3D treatment planning [16]. We infer that 3D treatment planning with 3-or 4-portals used in the IFI group might contribute to lower incidences of late toxicities.…”
Section: Discussionmentioning
confidence: 72%
“…Mackley et al report less toxicity with 3D-RT in comparison to 2D-RT in esophageal carcinoma, with no impact on survival. 18 Improved local control, OS, and less toxicity for 3D-RT has also been reported in other carcinomas, such as prostate and lung cancer. 17,19 In our study, patients treated with SC-RT had a poorer OS rate than patients treated with CF-RT.…”
Section: Discussionmentioning
confidence: 91%
“…In recent years, three-dimensional computed tomography (CB)-based radiotherapy planning (3D planning) has become the mainstream. Mackley et al [ 6 ] showed that the number of patients who had esophagitis was significantly smaller in patients for whom 3D planning was performed than in patients for whom 2D planning was performed. Moreover, the method of position matching for daily radiotherapy has been improving.…”
Section: Introductionmentioning
confidence: 99%